Curriculum as a Multistoried Process - Olson, Margaret (Canadian Journal of Education/Revue canadienne de l'éducation, 2000)
This study shows, through examples from preservice teachers’ practicum experi- ences, the pivotal role that teachers’ narrative knowledge plays in how curriculum is lived in classrooms. By listening to preservice teachers’ stories, I arrived at a holistic understanding of their practicum experiences. The student teachers nego- tiated, with some difficulty, their own curriculum narratives within the coopera- ting teachers’ narratives that were in place. I observed that by making spaces for narrative enquiry, spaces to make explicit and examine individual curriculum stories, cooperating teachers and preservice teachers can prompt growth and change within the practicum experience. Dans cet article, l’auteure montre le rôle clé des récits d’enseignants, lors des stages d’enseignement. En écoutant les témoignages des stagiaires, l’auteure est arrivée à une compréhension holistique de leurs expériences. Les futurs enseignants ont eu du mal à situer leurs propres récits par rapport à ceux des enseignants associés. L’auteure a remarqué qu’en faisant place aux récits des expériences de chacun par rapport au programme, les enseignants associés et les futurs enseignants peuvent apporter des améliorations et des changements lors des stages.